A Web-based Monitoring and Evaluation System for Government Projects in Tanzania: The Case of Ministry of Health - Mleke, M. N.; Dida, M. A. (Engineering, Technology & Applied Science Research, 2020)
Monitoring and evaluation systems are used by organizations or governments to measure, track progress, and evaluate the outcomes of projects. Organizations can improve their performance, effectiveness, and achieved results in project success by strengthening their monitoring and evaluation systems. Moreover, various studies reveal the need for information and communication technology systems in monitoring and evaluation activities. Despite the advantage of the tools, most organizations do not employ computerized monitoring and evaluation systems due to their cost and limited expertise whereas those having these systems lack a systematic alert mechanism of the projects’ progress. Currently, the Ministry of Health, Community Development, Gender, Elderly, and Children of Tanzania monitors and evaluates its projects manually facing the risks and consequences of delayed project completeness. In this study, the evolutionary prototyping approach was used to develop the proposed system. This study describes the development of a web-based monitoring and evaluation system that aims to solve the monitoring and evaluation challenges, simplify works, generate quality data, and provide timely successful project implementation. The developed system was tested and evaluated against the user’s requirements and was positively accepted to be deployed at the Ministry of Health.